The Use of Meher Language in Traditional Maso Minta Ceremonies in Oirleli Country, Romang Islands District Southwest Maluku Regency - Salmanu, Febrianti; Rumalean, Iwan; Lelapary, Heppy Leunard (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to find out and explain how people's views or perceptions regarding the decline in the number of Meher language use in Oireli Country, Romang Islands District, Southwest Maluku Regency. The research was conducted in order to help the community in describing the use of Meher language in traditional maso minta ceremonies in Oirleli Country, Romang Islands District, Southwest Maluku Regency. Meher language is the only mother tongue owned by the people of Oirleli Country, so the government requires the younger generation to learn and master the Meher language. The purpose of this study is to describe the use of Meher language in traditional maso minta ceremonies in Oirleli Country, Romang Islands District, Southwest Maluku Regency. The result of this study is that there are several factors that influence the decline in the use of Meher language. Based on the research that has been done, the results show that the people of Oirleli Country do not understand about the Meher language, many factors affect people's knowledge about the Meher language, including the lack of use of the Meher language in everyday life, the condition of the community, especially young people who are able to master two or more languages, does not take advantage of globalization in preserving culture, especially the Meher language, the phenomenon of migration that occurs among the community, inter-ethnic marriages that occur among the community, and lack of respect for their own ethnicity.